LOST TREASURE OF THE LANFANG REPUBLIC - Tan, Lip Hong (Singapore : Epigram Books, 2023)
What if the first modern republic in the world was not America or France but a gold-rich state founded in 1777 in the middle of West Kalimantan?
Keywords: Treasure hunting -- Fiction; Borneo -- Fiction